Kawasaki-like multisystem inflammatory syndrome associated with SARS-CoV-2 infection in an adult. Issue 7 (23rd July 2021) - Faller, Eamonn; Barry, Rachel; O'Flynn, Owen; Kearney, Peter; Sadlier, Corinna
Abstract : Kawasaki-like hyperinflammatory syndrome has been widely described as a manifestation of SARS-CoV-2 infection in paediatric patients. We report a compatible presentation and suggest that physicians consider the potential for this multisystem inflammatory syndrome to occur in adults. A 23-year-old man presented to hospital with a 4-day history of vomiting, diarrhoea, dry cough, fever and a blanching erythematous rash on hands, feet and buttocks. He was otherwise fit and healthy. On day 3 of admission, marked bilateral conjunctivitis developed and high sensitivity troponin I increased significantly, followed by acute respiratory compromise requiring high-flow nasal oxygen therapy. Transthoracic echocardiogram on day 5 showed severe global hypokinesis of the left ventricle with an ejection fraction of 22%. SARS-CoV-2 was not detected by reverse transcription PCR on nasopharyngeal swabs, sputum or stool samples, however, SARS-CoV-2 antibody was positive. The patient's syndrome resolved and cardiomyopathy reversed completely with supportive measures. He has since made a good recovery.